An Anchor-Based Localization in Underwater Wireless Sensor Networks for Industrial Oil Pipeline Monitoring - Nitin Goyal (7876730) (2022)
Industries need solutions that can automatically monitor oil leakage from deployed underwater pipelines and to rapidly report any damage. The location prediction of mineral reservoirs like oil, gas, or metals in deep water is a challenge during the extraction of these resources. Moreover, the problem of ores and mineral deposits on the seafloor comes into play. The abovementioned challenges necessitate for the deployment of underwater wireless sensor networks (UWSNs). Anchor-based localization techniques are segregated into range-free and range-based processes. Range-based schemes depend on various techniques like angle of arrival (AoA), time of arrival (ToA), time difference of arrival (TDoA), and received signal strength indicator (RSSI). In this article, the localization of these leakages is performed by using range-based metrics for calculating the distance among anchor nodes (ANs) and target nodes (TNs). This estimated distance is further optimized to minimize the estimation error. A multilateralism procedure is used to estimate the optimal position of each TN. The results exhibit that the proposed algorithm shows a high performance when compared to previous works, in terms of minimum energy consumption, lower packet loss, rapid location estimation, and lowest localization error. The benefit of using the proposed methodology greatly impacts on identifying the leakage area in mobility-assisted UWSN, where rapid reporting helps to lower the loss of resources. Les industries ont besoin de solutions permettant de surveiller automatiquement les fuites de pétrole des pipelines sous-marins déployés et de signaler rapidement tout dommage. La prédiction de l’emplacement des réservoirs de minéraux comme le pétrole, le gaz ou les métaux en eaux profondes est un défi lors de l’extraction de ces ressources. En outre, le problème des minerais et des dépôts minéraux sur le fond marin entre en jeu. Les défis mentionnés ci-dessus nécessitent le déploiement de réseaux de capteurs sans fil sous-marins (UWSN). Les techniques de localisation basées sur l’ancrage sont classées en deux catégories : les procédés sans portée et les procédés basés sur la portée. Les procédés basés sur la portée dépendent de diverses techniques comme l’angle d’arrivée (AoA), le temps d’arrivée (ToA), la différence de temps d’arrivée (TDoA) et l’indicateur de la force du signal reçu (RSSI). Dans cet article, la localisation de ces fuites est effectuée en utilisant des métriques basées sur la distance pour calculer la distance entre les nœuds d’ancrage (AN) et les nœuds cibles (TN). Cette distance estimée est ensuite optimisée pour minimiser l’erreur d’estimation. Une procédure multilatéralisme est utilisée pour estimer la position optimale de chaque TN. Les résultats montrent que l’algorithme proposé est très performant par rapport aux travaux précédents, en termes de consommation d’énergie minimale, de perte de paquets réduits, d’estimation rapide de la position et d’erreur de localisation minimale. L’avantage de l’utilisation de la méthodologie proposée a un impact important sur l’identification de la zone de fuite dans les UWSN á mobilité assistée, où un signalement rapide permet de réduire la perte de ressources. Other Information Published in: IEEE Canadian Journal of Electrical and Computer Engineering License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/icjece.2022.3206275